Association of Prepregnancy Cardiovascular Risk Factors Clusters with Stillbirth Risk Across Racial and Ethnic Groups: A Nationwide Population-Based Study of 31.4 Million Singleton Births and 131 047 Stillbirths - De Moraes-Ferrari, G (American Heart Association Inc., 2025)
BACKGROUND: The relationship between specific clusters of prepregnancy cardiovascular risk factors and stillbirth, particularly across racial and ethnic groups, remains understudied. We aimed to evaluate the association between 16 distinct cardiovascular risk clusters and stillbirth, emphasizing racial disparities.METHODS: We conducted a nationwide, population-based study using Centers for Disease Control and Prevention Natality and Fetal Death Data Files (2014–2022), including 31 408 776 singleton births and 131 047 stillbirths (≥20 weeks’ gestation). Prepregnancy cardiovascular risk factors—diabetes, hypertension, smoking, and nonideal body mass index—were categorized into 16 mutually exclusive clusters. Modified Poisson regression with robust variance estimation was used to estimate adjusted relative risks and 95% CIs.RESULTS: The analysis of the 16 groups defined by the 4 binary risk factors revealed that, compared with clusters without any risk factors, clusters with a single risk factor, absent the other 3, displayed varying degrees of stillbirth risk: prepregnancy diabetes posed the greatest risk (adjusted relative risk, 4.05 [95% CI, 3.74–4.39]), followed by prepregnancy hypertension (adjusted relative risk, 2.44 [95% CI, 2.27–2.63]), smoking (adjusted relative risk, 1.62 [95% CI, 1.58–1.67]), and unhealthy body mass index (adjusted relative risk, 1.33 [95% CI, 1.31–1.35]). The absolute excess risk attributable to biological interaction between 2 risk factors was observed in 2 of 6 risk combinations, predominantly those involving diabetes. Racial disparities were pronounced, with non-Hispanic Black mothers exhibiting the highest relative and absolute risks of stillbirth, nearly double that of non-Hispanic White mothers.CONCLUSIONS: Prepregnancy cardiovascular risk profiles are strongly associated with stillbirth, with marked racial and ethnic disparities. Simplified scoring systems may obscure heterogeneity in risk, reinforcing the need for race-conscious, targeted interventions. © 2025 The Author(s). Published on behalf of the American Heart Association, Inc., by Wiley. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.